Dynamics of the content of nutrients in winter barley plants depending on the variety, sowing dates and plant growth regulators - Zaiets, Serhii; Onufran, Lyudmila; Fundirat, Kateryna; Yuzyuk, Serhiі; Kisil, Lyudmila (Вісник аграрної науки Причорномор'я, 2022)
The problem of increasing the production of winter barley grain on irrigated lands can be solved thanks to the improvement of the varietal composition, optimization of sowing dates and improvement of the nutrition system, in particular through the use of drugs with growth-regulating properties. Taking into account the important biological role of growth regulators in the plant nutrition system, the aim was to determine the influence of Gummifield Forte brix, MIR and PROLIS on the content of nitrogen, phosphorus and potassium in the main phases of plant development of different varieties of winter barley at optimal and late sowing dates. The research was conducted at the Institute of Irrigated Agriculture (now the Institute of Climate-Oriented Agriculture) of the National Academy of Sciences according to methodological recommendations for conducting field tests under irrigation conditions. In the above-ground mass of plants, straw and grain, the total content was determined: nitrogen – according to Kjeldahl, phosphorus – according to Murphy-Reilly, potassium – using a flame photometer. It was determined that on the irrigated lands of the South of Ukraine, the use of growth regulators Gumifield Forte brix, MIR and PROLIS had a significant effect on the accumulation of the main nutrients (especially nitrogen) by plants and winter barley grains. The highest content of basic nutrients in plants was at the early stages of development (spring tillering), after which their amount decreased until the end of the growing season of the crop. The maximum nitrogen content of 2.02% on dry matter on the Dev'iatyi val variety and 1.85% on the Academichnyi variety was provided by the use of Gummifield Forte Brix.Among the varieties, the Dev'iatyi val, on average, accumulated nitrogen in the grain for sowing on October 1 and 20 by 9.1 and 9.5 percentage points more than Akademichnyi, according to the plant growth regulator factor. Thanks to the treatment of winter barley seeds with plant growth regulators Gumifield Forte Brix and PROLIS and sowing the crop at the optimal time, it is possible to increase the nitrogen content in plants and grain by 6.0-15.1 and 9.3-22.5 percentage points, respectively, which will have a positive effect on grain formation and its quality. In further studies, it is necessary to optimize the application doses of mineral fertilizers using new multi-component growth regulators of winter barley plants under irrigation conditions in the South of Ukraine